Global perspectives on income taxation law - Avi-Yonah, Reuven S. (Reuven Shlomo), 1957-; Sartori, Nicola; Marian, Omri. (New York ; Oxford : Oxford University Press, 2011)
In 'Global Perspectives on Income Taxation Law', Avi-Yonah covers basic, corporate and international tax law from a comparative perspective. The book both supplements readings in U.S. tax law courses and serves as a textbook for a comparative tax law class.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Income tax -- Law and legislation